2011
DOI: 10.1242/dev.066118
|View full text |Cite
|
Sign up to set email alerts
|

Concerted involvement of Cdx/Hox genes and Wnt signaling in morphogenesis of the caudal neural tube and cloacal derivatives from the posterior growth zone

Abstract: There was an error in the ePress version of Development 138, 3451-3462 published on 13 July 2011.The first names of one of the authors were listed incorrectly. The final print and online versions are correct, and the correct author list appears above.The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 86 publications
2
40
0
Order By: Relevance
“…In addition however, a set of ∼240 genes appeared uniquely upregulated in NMP cells (Table S1). These included the transcription factors Brachyury , Nkx1.2 (also known as Sax1 ), which is expressed in the stem zone of midgestation embryos [50],[51] Mixl1 [52], Wnt3a and Cdx2 which are expressed in the primitive streak and nascent mesoderm [32],[33]. In addition Follistatin , which plays a key role in neural induction by blocking TGFβ signalling [53] and components of the Fgf signalling pathway, which is implicated in mesoderm induction [16], are upregulated in NMPs (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition however, a set of ∼240 genes appeared uniquely upregulated in NMP cells (Table S1). These included the transcription factors Brachyury , Nkx1.2 (also known as Sax1 ), which is expressed in the stem zone of midgestation embryos [50],[51] Mixl1 [52], Wnt3a and Cdx2 which are expressed in the primitive streak and nascent mesoderm [32],[33]. In addition Follistatin , which plays a key role in neural induction by blocking TGFβ signalling [53] and components of the Fgf signalling pathway, which is implicated in mesoderm induction [16], are upregulated in NMPs (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…These signals are required for body axis elongation [16] and both Wnt and Fgf signalling have been implicated in mesoderm and neural induction [22],[25]–[31]. In vivo and in vitro evidence has suggested that Wnt signalling is responsible for posteriorising tissue by inducing posterior Hox genes [29],[32],[33]. Together, the data suggest that the generation of posterior neural tissue and paraxial mesoderm proceeds by Wnt and Fgf signalling inducing a neuromesodermal bipotential intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the Cdx genes block the induction of posterior Hox genes and impair axial extension in embryos (Savory et al., 2009, Young et al., 2009, van de Ven et al., 2011, van Rooijen et al., 2012, Amin et al., 2016, Neijts et al., 2016). The truncation of the body axis can be partially rescued by exposure to Wnt or FGF signaling (Young et al., 2009, van Rooijen et al., 2012, van de Ven et al., 2011). Nevertheless, although the induction of Wnt3a , Fgf8 , and T/Bra by Cdx proteins have been implicated in these phenotypes, the severity of morphological defects in mutant embryos has made it difficult to establish the relative importance of target genes and to rule out others.…”
Section: Discussionmentioning
confidence: 99%
“…These regions express Wnt and FGF ligands (Wilson et al., 2009). Interfering with either signal results in the depletion of NMPs and the premature truncation of the body axis (Takada et al., 1994, Wilson et al., 2009, Yoshikawa et al., 1997, van de Ven et al., 2011). Both Wnt and FGF signaling are implicated in posteriorizing cells by inducing the Cdx transcription factors (TFs) that promote the expression of more posterior Hox genes (van den Akker et al., 2002, Nordstrom et al., 2006, van de Ven et al., 2011, Mazzoni et al., 2013, Neijts et al., 2016, Amin et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation